Study on n-acetylcysteine in prevention in nephropathy in patients undergoing coronary angiography In HUSM - Mohamed, Wan Mohd lzani Wan (Pusat Pengajian Sains Perubatan, 2011)
Objective: Contrast induced nephropathy (CIN) is defined as acute renal failure within 48 hours of exposure to radiographic contrast media in the absence of other underlying aetiology. The role of oral N-acetylcysteine in prevention of CIN has not been established. This study is aimed to assess the efficacy of oral N-acetylcysteine in prevention of CIN and to determine the associated risk factors of the development of CIN. Design: Randomised controlled trial. Materials and methods: We prospectively studied 100 patients with renal impairment (mean serum creatinine 124.1 ± 19.68 pmol/1) who underwent elective. diagnostic or therapeutic coronary angiography. Patients were randomly assigned to receive either N-acetylcysteine (600mg orally BD for 4 doses) with 0.45% saline hydration (NAC group) or 0.45% saline alone (control group). Serum creatinine was measured before angiogram, 24 and 48 hours after coronary angiogram. Results: An increase of> 25% in the baseline creatinine Ievel48 hours after the procedure occurred in 2 of 49 (4.1 %) patients in NAC group aud 6 of 51 (11;8'YQ)·piltients in control group. The difference was not statistically significant (p = 0.269). The baseline serum creatinine concentration in both groups were similar (123.7 ± 17.08 l'moVl in NAC group and 124.4 ± 21.89 I' mol/1 in Control group). Changes of serum creatinine after 24 and 48 hours of coronary angiography were uot significant between the two treatment groups (p = 0.821). The only significant risk factor for the development of CIN was the contrast volume (mean diff -ll2.44, 95% CI -184.22, - 40.66, p = 0.002). Conclusion: Addition of N-acetylcysteine to standard hydration therapy is not associated with reduction in incidence of CIN in patients with mild to moderate renal impairment undergoing elective coronary angiography. The amount of contrast agent is a significant predictor of renal function deterioration and incidence of CIN post coronary angiography.